BIOESTRATIGRAFIA DEL ORDOVICICO (LLANVIRNIANO-LLANDEILIANO) DE LA SIERRA DEL TONTAL, PRECORDILLERA DE SAN JUAN. DESCRIPCION DE SU FAUNA GRAPTOLITICA. (Ameghiniana, 2013)
An Ordovician sequence (Llanvimian-Llandeilian) located in the orographíc axis of the Precordillera of San Juan has been recognized. The region embraces the strip of hígh summits and the western watershed of Sierra del Tontal. The stratigraphic sequence, of about 1.500-2.000 m thick, is composed of psamo-pelitic turbidites succession with subordinated lensoid conglomerates. The depositional environment corresponds to the continental edge. It is assurned that the turbidite succession belongs to a submarine fan. An important graptolite fauna has been recognized in some of the turbidite beds. It is composed of: Retiograptus geinitzianus Hall, Cryptograptus antennarius (Hall), Glossograptus hincksii (Hopkinson ), Glossograptus cf. G. armatus Nicholson, Paraglossograptus aff. P. tentaculatus (Hall), Dicellograptus cf. D. moffatensis Carruthers, Climacograptus aff. C. parvul Hall, Climacograptus cf. C. brevis Elles & Wood, Arnplexograptus aff. A. arcstus Elles y Wood, Amplexograptus minutus sp. nov., Gliptograptus cf. G. teretiusculus (Hisínger ), Glyptograptus dentatus Brongniart, Glyptograptus cf. G. intersitus Harris & Thomas, Glyptograptus austrodentatus Harris & Keble and Didymograptus sp.